Computational study of the stable atomic trapping sites in Ar lattice - Ozerov, G.K.; Bezrukov, D.S.; Buchachenko, A.A. (Физика низких температур, 2019)
Stable atomic trapping sites in the Lennard-Jones face-centered cubic Ar crystals are investigated by means
of the global optimization strategy and convex hull concept for thermodynamic stability. Five generic site types
are found in full accord with crystallographic intuition: interstitial within tetrahedral and octahedral hollows
and substitutions, single, tetra- and hexavacancy. Their identities are established by radial distribution function
analysis. Stability regions of these sites are mapped into the space of Lennard-Jones parameters of the guest–host
interatomic interaction. Predictions made for the number and types of the stable sites for selected atoms (H, Mn,
Na, Yb, Eu, Ba) are found to be in line with the results of more sophisticated models and matrix isolation spectroscopy experiments. Stable atomic trapping sites in the Lennard-Jones face-centered cubic Ar crystals are investigated by means
of the global optimization strategy and convex hull concept for thermodynamic stability. Five generic site types
are found in full accord with crystallographic intuition: interstitial within tetrahedral and octahedral hollows
and substitutions, single, tetra- and hexavacancy. Their identities are established by radial distribution function
analysis. Stability regions of these sites are mapped into the space of Lennard-Jones parameters of the guest–host
interatomic interaction. Predictions made for the number and types of the stable sites for selected atoms (H, Mn,
Na, Yb, Eu, Ba) are found to be in line with the results of more sophisticated models and matrix isolation spectroscopy experiments. Для исследования стабильных ловушек атомов в гранецентрированной кубической решетке аргона, моделируемой потенциалами Леннарда-Джонса, использованы методы
глобальной оптимизации и оценки термодинамической устойчивости по методу выпуклых оболочек. В полном соответствии с интуитивными кристаллографическими соображениями обнаружены ловушки пяти общих типов: внедрения
в тетраэдрическую и октаэдрическую полости решетки, замещение ее узла и замещения четырех- и шестиатомных вакансий. Индивидуальность этих типов установлена в результате анализа радиальных функций распределения атомов
решетки. Представлены карты областей устойчивости ловушек всех типов в пространстве параметров взаимодействия
Леннарда-Джонса между захваченным атомом и атомом решетки. Предсказания числа и типов устойчивых ловушек
атомов H, Mn, Na, Yb, Eu и Ba, полученные на основе карт,
согласуются с результатами более точных моделей и доступных экспериментов по матричной изоляции.